China 2030 : Building a Modern, Harmonious, and Creative Society - World Bank; Development Research Center of the State Council, the People’s Republic of China (Washington, DC: World Bank, 2013)
China's economic performance over the past 30 years has been remarkable. The report is based on the strong conviction that China has the potential to become a modern, harmonious, and creative high income society by 2030. The report proposes six strategic directions for China's new development strategy: 1) rethinking the role of the state and the private sector to encourage increased competition in the economy; 2) encouraging innovation and adopting an open innovation system with links to global research and development networks; 3) looking to green development as a significant new growth opportunity; 4) promoting equality of opportunity and social protection for all; 5) strengthening the fiscal system and improving fiscal sustainability; and 6) ensuring that China, as an international stakeholder, continues its integration with global markets.